Burnout nos profissionais de saúde mental: expectactivas, auto-actualização e outras variáveis associadas - Magda Oliveira (2004)
The objective of this study with 55 mental health workers was twofold: analyze some individual variables that could be associated to burnout and analyze some of its consequences. Concerning burnout, results show scores below the mean scores reported for this type of population; concerning individual variables associated to burnout some non-significant correlations were found between expectations and burnout, as well as between workers self-actualization and burnout. Concerning demographic variables it was found correlations between gender, age, multiple jobs and time in task. In addition a highly significant correlation was found between burnout and some organizational variables. Burnout consequences were deducted through the correlations (although non-significant) between burnout scores and the intensity of felt stress, as well as between burnout scores and turnover, absenteeism, and familial and social relationships difficulties. In order to obtain more conclusive results we propose a replication of the study with a greater and more homogeneous sample concerning the distribution of workers groups.